Ghana cereal-legume agronomy scaling and acceleration platform (Gh-CerLeg-GAIP) - Adjei-Nsiah, S.; Nkomo, M.; Dotse, S.K.; Vincent, A.; Ndejipo, I. (International Institute of Tropical Agriculture, 2023)
The EiA 2030 Initiative aims to deliver agronomic gain at scale for sustainable intensification of smallholder farming systems in the global south, co-created by CGIAR centers and strategic scaling partners from the public and private sectors. The Cereal-Legume Agronomy Scaling and Acceleration Platform (GH-CerLeg-GAIP) initiative of the Consultative Group on International Agricultural Research (CGIAR) Workshop was organized for the EiA 2030 Northern Ghana Soybean and Maize Agronomy Platform in Tamale on 15-17 August 2023 at Mariam Hotel, Tamale. The initiative’s overall goal is “To reduce yield gap, increase resource use efficiency and respond to climate-related stresses in major farming systems at scale”. The workshop’s objectives were to Map soybean and maize value chain actors in Northern Ghana, establish value chain strategic priorities (with emphasis on Agronomic Solutions) in a changing environment, and Develop innovation packages for scaling-ready agronomic innovations. The workshop was attended by 50 participants (47 men and 3 women) drawn from the key actors along the soybean/maize value chain. These included Directors of Agriculture, CSIR-Savanna Agricultural Research Institute representatives, YARA-Ghana, Aggregators, Nucleus farmers, Esoko Ghana and IITA. The 3-day workshop adopted a participatory approach using tools such as PowerPoint presentations for information sharing, group work, and plenary discussions for GH-CerLeg-GAIP development. Emerging issues were prioritized, synthesized, and presented by stakeholders with agronomic challenges identified, enablers, and solutions proposed to deepen their understanding of innovation readiness and use assessments.